2021
DOI: 10.1017/pls.2020.29
|View full text |Cite
|
Sign up to set email alerts
|

Concerns regarding Covid-19 vaccine certificates

Abstract: Besides vaccine certificates, research suggests leaders also need to trigger society’s intrinsic motivation to help in order to achieve lasting and equitable solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…A study comparing Israel (where VP was adopted) and UK respondents found that domestic vaccine passports may negatively affect people’s autonomy, motivation, and willingness to get vaccinated [ 44 ]. The finding was consistent with the suggestion that besides vaccine certificates, public health officials should also trigger people’s intrinsic motivation to address the pandemic [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study comparing Israel (where VP was adopted) and UK respondents found that domestic vaccine passports may negatively affect people’s autonomy, motivation, and willingness to get vaccinated [ 44 ]. The finding was consistent with the suggestion that besides vaccine certificates, public health officials should also trigger people’s intrinsic motivation to address the pandemic [ 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interventions that involve enforcement of vaccination, for example, vaccine passports as a requirement to access social liberties, can potentially be effective if implemented well but also carry the risks of increasing health inequalities and being viewed as coercive (Brown et al, 2020 ; Waller et al, 2020 ). In contrast, interventions that focus on addressing vaccine hesitancy through increasing intrinsic motivation, encouraging pro‐social behaviour, and increasing empathy are likely to be useful and acceptable in the longer term (Chou & Budenz, 2020 ; Freeman et al, 2020 ; Pfattheicher et al, 2020 ; Spisak & McNulty, 2021 ). The personal risk of harm from COVID‐19 to most individuals is low and people's actions are likely to be influenced by perceived risk to others (Faasse & Newby, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the COVID-19 pandemic, the function of mass media is of the utmost importance (Hussain, 2020). Mass media plays a critical role in delivering the public message through a stream of communication that guides the audience's attitude towards the COVID-19 vaccination (Wang et al, 2020) and their attitude towards a COVID-19 vaccine certificate (Spisak and McNulty, 2021). Reiter et al (2020) argue that public opinion leaders influence attitudes towards accepting the COVID-19 vaccine.…”
Section: Hypothesis Developmentmentioning
confidence: 99%